Short chain fatty acids increase fat oxidation and promote browning through β3-adrenergic receptor/AMP-activated protein kinase α signaling pathway in 3T3-L1 adipocytes. (April 2023) - Zhang, Wenkai; Kong, Li; Zhong, Zhen; Lin, Lezhen; Li, Jingen; Zheng, Guodong
Graphical abstract: Highlights: SCFAs regulate the expression of fatty acid oxidation to reduce lipid accumulation. SCFAs affect the biogenesis and quantity of mitochondria to promote thermogenesis. SCFAs up-regulate brown/beige specific markers to inhibit lipid deposition. SCFAs promote brown/beige adipocyte-like phenotype by β3-AR/AMPKα signaling pathway. Abstract: To investigate the molecular mechanism of short chain fatty acids (SCFAs) on promoting fatty acid β-oxidation and browning in 3T3-L1 adipocytes. SCFAs significantly reduced lipid accumulation in 3T3-L1 adipocytes. In addition, via increasing the expression of Tfam and Nrf1, SCFAs enhanced mitochondrial biogenesis. According to the results of qPCR analysis, the expression levels of fatty acid β-oxidation genes ( PPARα, CPT1α, ACOX1 ) were up-regulated by SCFAs. Moreover, SCFAs treatment increased the genes and proteins expression of brown adipocyte-specific factors such as PRDM16, PGC-1α, and UCP-1, as well as up-regulated the genes expression of beige adipocytes markers ( Tmem26, Tbx1, CD137, and Cited1) . Furthermore, the effects of β3-AR and AMPK antagonist were reversed by SCFAs. In conclusion, SCFAs promote fat β-oxidation and browning of adipocytes through β3-AR/AMPKα signaling pathway, thereby reducing fat accumulation in 3T3-L1 adipocytes. Therefore, SCFAs may be a helpful supplement to combat obesity.